The origins of the antitrust movement: An Interest-Group Perspective - Lanza, Joao Felipe Rodrigues; DiLorenzo, Thomas J. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
Several contemporary studies have highlighted the need to introduce competition in the transport, energy industries, as well as other markets held to be natural monopolies due to the inefficiency generated by government-regulated monopolies. However, little has been studied on the consequences of the regulation known as antitrust law; it dates back to a protectionist political process from the late 19th century, which laid the foundations for most government regulation on several industries accused of monopoly practices. The present article has studied the origins of the antitrust movement as a political initiative, analyzed the evidences of the industries accused of monopolization, and has proven the research hypothesis that antitrust laws and their derivatives have actually restricted competition more than improved market performance by correcting alleged “market failures”.